2013
DOI: 10.1074/jbc.m113.523340
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of the Hypoxanthine/Guanine Transporters YjcD and YgfQ and the Adenine Transporters PurP and YicO of Escherichia coli K-12

Abstract: Background: Four putative purine transporter genes represent a distinct homology cluster within family NCS2 in Escherichia coli. Results: The four genes encode high affinity transporters for adenine or hypoxanthine/guanine with essential residues at the same consensus sites as in xanthine/uric acid-transporting homologs. Conclusion: Distantly related purine transporters use topologically similar selectivity determinants. Significance: Our study provides the first structure-function insight on the cluster of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
1
57

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(133 citation statements)
references
References 39 publications
6
69
1
57
Order By: Relevance
“…As a result, homology modeling has been used as a reasonable alternative in cases where no x-ray structure is available (23,48,59,61,(67)(68)(69)(70)(71)(72)(73). Using this approach, combined with induced fit docking and a detailed characterization of the specificity profile, we identified 9 residues that are important for PrnB function, Gly 56 Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, homology modeling has been used as a reasonable alternative in cases where no x-ray structure is available (23,48,59,61,(67)(68)(69)(70)(71)(72)(73). Using this approach, combined with induced fit docking and a detailed characterization of the specificity profile, we identified 9 residues that are important for PrnB function, Gly 56 Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, to initiate the metabolism of the starved spirochetes, the bacteria were preincubated at 37°C for 30 min in 1-ml reaction volumes containing HN buffer (50 mM HEPES and 50 mM NaCl, pH 7.4), 6 mM glucose, and 1.4% rabbit serum (Pelfreez). This amount of rabbit serum was estimated to contain ϳ90 nM hypoxanthine and ϳ5 nM adenine (19,20) 15 Ci/mmol) (PerkinElmer), and samples were analyzed at 10, 20, 30, 45, and 60 s following the addition of radioactivity. The rates of purine uptake (fmol/5 ϫ 10 7 spirochetes/s) were estimated for each purine concentration by linear regression, and the K m values were determined using GraphPad Prism, version 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, structure-function analyses of the E. coli adenine-specific permeases PurP and YicO and hypoxanthine-guanine-specific permeases YjcD and YgfQ as well as the A. nidulans adeninehypoxanthine-guanine permease AzgA identified key amino acid residues critical for purine uptake activity (13,15). Both of these studies identified an aspartic acid and a glutamic acid residue (Asp339 and Glu394 in AzgA) to be essential for the transport function for all five COG2252 family members (13,15). These residues are conserved in BBB22 and BBB23.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations